Genome-wide identification and expression analysis of protein arginine methyltransferase and JmjC domain-containing family in apple - Su, Shenghui; Ji, Min; Chen, Jiaqi; Zhang, Meidie; Xu, Xiaozhao; Cheng, Chenxia (Frontiers in Plant Science, 2024)
Histone methylation is an important type of histone modification that regulates gene expression in plants. In this study, we identified 14 arginine methylation-related genes (Protein Arginine Methyltransferase, MdPRMT) and 32 demethylation-related genes (JmjC Domain-Containing Family, MdJMJ) in apple. Furthermore, we investigated the phylogenetic relationship, chromosome distribution, gene structure, motif analysis, promoter sequence analysis, and expression patterns of MdPRMT and MdJMJ genes. Homology analysis showed a high degree of conservation and homology between PRMT and JMJ genes in Arabidopsis and apple. We identified the types of duplicated genes in the MdJMJ and MdPRMT gene families, found a large number of whole-genome duplicates (WGD) gene pairs and a small number of tandem duplicates (TD) pairs, transposed duplication (TRD) gene pairs as well as proximal duplicates (PD) pairs, and discussed the possible evolutionary pathways of the gene families from the perspective of duplicated genes. Homology analysis showed a high degree of conservation and homology between PRMT and JMJ genes in Arabidopsis and apple. In addition, the promoter regions of MdPRMT and MdJMJ contain numerous cis-acting elements involved in plant growth and development, hormone response, and stress responses. Based on the transcriptional profiles of MdPRMT and MdJMJ in different tissues and developmental stages, it was found that MdPRMT and MdJMJ may play multiple roles in apple growth and development, for example, MdJMJ21 may be involved in the regulation of apple endosperm formation. MdPRMT and MdJMJ exhibit different expression patterns in response to hormone signaling in apple, MdJMJ3, MdJMJ18, MdJMJ30, MdPRMT2, MdPRMT13, and MdPRMT14 may play roles in apple response to drought stress, while the expression of MdJMJ13, MdPRMT3, MdPRMT4, and MdPRMT6 is affected by cold stress. Our study provides a foundation for determining the functional roles of MdPRMT and MdJMJ genes in apple.